The European educational space as a factor for changes in the school management system - Semenyuk, Yuriy; Kolisnichenko , Natalia (Theory and Practice of Public Administration, 2019)
The paper examines the impact of the European educational space on the national secondary education management systems. The idea of the European educational space as a reflection of multilevel governance in education is explored. National, supranational and transnational educational policy actors are considered. The emergence and development of the idea of "Europeanization" of education are revealed. As an integral process of formation of educational space in Europe, the peculiarity of expanding public participation in the decision-making on education is substantiated. In particular, various forms of public governance in the system of secondary education are considered: school boards, boards of school principals, parents boards, self-governance of students and so on.